Health belief model for coronavirus infection risk determinants - Marcelo Fernandes Costa
ABSTRACT OBJECTIVE To use the advantages of a ratio scale with verbal anchors in order to measure the risk perception in the novel coronavirus infection, which causes covid-19, in a health belief model-based questionnaire, as well as its validity and reproducibility. METHOD We used the health belief model, which explores four dimensions: perceived susceptibility (five questions), perceived severity (five questions), perceived benefits (five questions), and perceived barriers (five questions). Additionally, we included a fifth dimension, called pro-health motivation (four questions). The questions composed an electronic questionnaire disseminated by social networks for an one-week period. Answers were quantitative values of subjective representations, obtained by a psychophysically constructed scale with verbal anchors ratio (CentiMax ® ). Mean time for total filling was 12 minutes (standard deviation = 1.6). RESULTS We obtained 277 complete responses to the form. One was excluded because it belonged to a participant under 18 years old. Reproducibility measures were significant for 22 of the 24 questions in our questionnaire (Cronbach's α = 0.883). Convergent validity was attested by Spearman-Brown's split half reliability coefficient (r = 0.882). Significant differences among groups were more intense in perceived susceptibility and severity dimensions, and less in perceived benefits and barriers. CONCLUSION Our health belief model-based questionnaire using quantitative measures enabled the confirmation of popular beliefs about covid-19 infection risks. The advantage in our approach lays in the possibility of quickly, directly and quantitatively identifying individual belief profiles for each dimension in the questionnaire, serving as a great ally for communication processes and public health education.